Peierls stress in face-centered-cubic metals predicted from an improved semi-discrete variation Peierls-Nabarro model. (15th July 2016) - Liu, Guisen; Cheng, Xi; Wang, Jian; Chen, Kaiguo; Shen, Yao
Abstract: In order to quantitatively predict Peierls stress, a semi-discrete variational Peierls-Nabarro model is improved by incorporating an additional gradient energy term into the energy functional. This gradient energy term is designed to effectively represent the influence of both the discreteness of atoms and the quick variations of the displacement profile in the dislocation core. Using face-centered-cubic metals as a model system for validation, we obtain a more accurate prediction of the displacement profile across the slip plane, and consequent precise Peierls stress, within a few times the prediction from molecular dynamics calculations. Graphical abstract: